Comparison Effectiveness of Health Promotion using Video and Metaphor to Level of Knowledge of Pregnant Woman about Stunting in Palembang - Stellanisa Nagari (Community Medicine and Education Journal, 2021)
Mother’s knowledge about risk factors of stunting are one of many efforts to prevent stunting. Health promotion could contribute to increase level of knowledge about stunting. Commonly used methods are video and speech. This study was conducted to compare effectiveness of health promotion using video and metaphor to level of knowledge of pregnant woman about stunting in Palembang. This sudy was a quasi-experimental nonequivalent control group pretest-posttest. Population are pregnant woman in Palembang. Samples was obtained by purposive sampling. The research data was collected by questionnaire. Pretest and posttest data was analyzed by Wilcoxon. Effectiveness of health promotion method valued by difference of pretest and posttest score between methods using Mann Whitney. Result of the study was significantly increasing knowledge of pregnant woman about stunting after health promotion (p=0,000). The most effective method of health promotion is video with p-value 0,05. Health promotion could increase knowledge of pregnant woman about stunting. Effective method for health promotion was video better than metaphor.